Leak localization using empirical mode decomposition and teager-kaiser energy operator analysis based on pressure transient signal: experimental study - Pi Remli, Mohd Aminuddin; Ghazali, M. F.; Azmi, W. H.; Mohd Yusof, M. F.; M. Yusop, Hanafi; Azmi, M. L. (IOP Publishing, 2019)
Leak detection become crucial part in water management services due to strenuous work in identification of leak location for pipeline networks. This paper focused on leak identification and localization using Teiger-Kaiser Energy Operator (TKEO) as instantaneous frequency analysis (IFA) while Empirical Mode Decomposition (EMD) as decomposition method with implementation of Integrated Kurtosis Algorithm for Z-Filter (Ikaz) to Kurtosis ratio as the automatic selection criterion for intrinsic mode function (IMF). Test rig construct inside laboratory as testing site using 67.90-metre Medium Density Polyethylene (MDPE) pipe In order to create an artificial leak, pinhole is drill at 19.75-metre distance from point of analysis that is fire hydrant attached with pressure sensor. Experiment conduct by using two variation of pressure that are 2bar and 4bar. As the result, with percentage of error less than 6%, combination of TKEO as IFA and efficiency of Ikaz performed well in locating the position of leak and outlet of pipeline system.